2014
DOI: 10.1002/ijc.28684
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic clustering of lung adenocarcinomas based on DNA methylation profiles in adjacent lung tissue: Its correlation with smoking history and chronic obstructive pulmonary disease

Abstract: The aim of this study was to clarify the significance of DNA methylation alterations during lung carcinogenesis. Infinium assay was performed using 139 paired samples of non-cancerous lung tissue (N) and tumorous tissue (T) from a learning cohort of patients with lung adenocarcinomas (LADCs). Fifty paired N and T samples from a validation cohort were also analyzed. DNA methylation alterations on 1,928 probes occurred in N samples relative to normal lung tissue from patients without primary lung tumors, and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 40 publications
6
53
0
Order By: Relevance
“…A smaller study focused on the methylation patterns of tumor suppressor genes reported that p16 was more commonly methylated in never smokers than current or former smokers [29]. A different study showed that heavy smokers, light smokers and never smokers separated into different groups based on an unsupervised hierarchical clustering analysis of DNA methylation levels [30]. Additionally, work from The Cancer Genome Atlas identified three sets of CpG island methylator phenotype (CIMP) samples: high, intermediate and low.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study focused on the methylation patterns of tumor suppressor genes reported that p16 was more commonly methylated in never smokers than current or former smokers [29]. A different study showed that heavy smokers, light smokers and never smokers separated into different groups based on an unsupervised hierarchical clustering analysis of DNA methylation levels [30]. Additionally, work from The Cancer Genome Atlas identified three sets of CpG island methylator phenotype (CIMP) samples: high, intermediate and low.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of expression was particularly prevalent among samples for IRX2. Interestingly, IRX2 has been suggested to function in lineage-specific epithelial cell differentiation in the breast tissue and to act as a tumor suppressor or oncogene depending on the cellular and tissue context [54][55][56][57][58][59][60][61]. Therefore, we used infection with lentiviral expression constructs to restore IRX2 in HL60 and AML-193 cell lines to determine the gene's impact on differentiation block in AML.…”
Section: Ectopic Expression Of Irx2 Promotes Differentiation In Aml Cmentioning
confidence: 99%
“…11 In NSCLC, hypermethylation at CpG-dense sequences in gene promoters (CpG islands) is associated with cigarette smoking 12 , histological subtype 13, 14 , progression 15, 16 , clinically-relevant molecular subtypes 17, 18 , and patient prognosis 19, 20 . Here, from genome-wide screening of differential DNA methylation in adjacent tumor and non-tumor tissues from three cohorts, HOXA9 promoter methylation emerged as a candidate prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%